The effect of StarD13 on lung cancer proliferation, motility, and invasion. (c2018) - Rif, Rayane E. El (2018)
Lung cancer is the second most commonly occurring cancer among both men and women, leading to 26% of all cancer-related deaths. Smoking is the, by far, the leading cause of lung cancer, and cessation is the most effective prevention method. The ability to metastasize and spread to distant locations in the body render a tumor more aggressive. Metastasis depends on the cell’s migratory ability, which requires the timely and coordinated regulation of the actin cytoskeleton. Rho GTP-ases are small GTP binding proteins that are known to play an essential role in cell migration. Rho GTP-ases are regulated by proteins known as GAPs (GTPase-activating proteins), GEFs (Guanine nucleotide exchange factors), and GDIs (Guanine nucleotide dissociation inhibitors). StarD13, also known as START-GAP2 or DLC2, is a protein with a known Rho-GAP function. It was previously found to act as tumor suppressor in astrocytoma, colon , and breast cancer. In this study, we looked at the role played StarD13 in lung cancer, by observing the effect of its down regulation on cell proliferation, 2D migration, invasion and adhesion. Our results show that StarD13 is in fact a tumor suppressor in lung cancer cells, having a negative regulatory effect on cell proliferation and invasion. However, and consistent with previous observations in other cancer types, StarD13 was found to be needed in cell 2D migration due to its regulation of focal adhesions detachment, without which the cell is stuck and cannot move forward. Our study looks into the tumor suppressor role of StarD13.